Ultrasound-guided Pulsed Radiofrequency Lesioning of the Phrenic Nerve in a Patient with Intractable Hiccup - Kang, Keum Nae (The Korean Pain Society, 2010)
Persistent and intractable hiccups (with respective durations of more than 48 hours and 1 month) can result in depression, fatigue, impaired sleep, dehydration, weight loss, malnutrition, and aspiration syndromes. The conventional treatments for hiccups are either non-pharmacological, pharmacological or a nerve block treatment. Pulsed radiofrequency lesioning (PRFL) has been proposed for the modulation of the excited nervous system pathway of pain as a safe and nondestructive treatment method. As placement of the electrode in close proximity to the targeted nerve is very important for the success of PRFL, ultrasound appears to be well suited for this technique. A 74-year-old man suffering from intractable hiccups that had developed after a coronary artery bypass graft and had continued for 7 years was referred to our pain clinic. He had not been treated with conventional methods or medications. We performed PRFL of the phrenic nerve guided by ultrasound and the hiccups disappeared.